Vaccine development for mosquito-borne viral diseases - Huang, Zhiwei; Zhang, Yuxuan; Li, Hongyu; Zhu, Jiajie; Song, Wanchen; Chen, Keda; Zhang, Yanjun; Lou, Yongliang (Frontiers in Immunology, 2023)
Mosquito-borne viral diseases are a group of viral illnesses that are predominantly transmitted by mosquitoes, including viruses from the Togaviridae and Flaviviridae families. In recent years, outbreaks caused by Dengue and Zika viruses from the Flaviviridae family, and Chikungunya virus from the Togaviridae family, have raised significant concerns for public health. However, there are currently no safe and effective vaccines available for these viruses, except for CYD-TDV, which has been licensed for Dengue virus. Efforts to control the transmission of COVID-19, such as home quarantine and travel restrictions, have somewhat limited the spread of mosquito-borne viral diseases. Several vaccine platforms, including inactivated vaccines, viral-vector vaccines, live attenuated vaccines, protein vaccines, and nucleic acid vaccines, are being developed to combat these viruses. This review analyzes the various vaccine platforms against Dengue, Zika, and Chikungunya viruses and provides valuable insights for responding to potential outbreaks.